Waqf in the Perspective of Waqf Rules in Indonesia - Hartanto, Selamet; Retnowati, May Shinta; Sup, Devid Frastiawan Amir (University of Darusssalam Gontor, 2021)
For Muslims in Indonesia, the basic concept of waqf in Islam is very well understood, and more than that, if examined further, there will be many waqf assets in Indonesia. In the perspective of a country, it is necessary to implement regulations, including Waqf Law (Law), Government Regulation (PP) on Waqf, Regulation of the Indonesian Waqf Board (BWI), and Regulation of the Minister of Religion (PMA). This study aims to explain waqf from the perspective of waqf rules in Indonesia. This research uses qualitative-descriptive-literature methods. The conclusion is that the existing waqf rules that apply in Indonesia aim to maintain the existence of waqf to always be in accordance with the basic concept of waqf in Islam. In addition, this rule also serves as the basis for the legal protection of legality of waqf in Indonesia.